2019
DOI: 10.2478/hukin-2019-0028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Far‐Infrared Emitting Ceramic Material Clothing on Recovery After Maximal Eccentric Exercise

Abstract: The purpose of this study was to determine whether Far-Infrared Emitting Ceramic Materials worn as Bioceramic pants would improve neuromuscular performance, biochemical and perceptual markers in healthy individuals after maximal eccentric exercise. Twenty-two moderately active men were randomized into Bioceramic (n = 11) or Placebo (n = 11) groups. To induce muscle damage, three sets of 30 maximal isokinetic eccentric contractions of the quadriceps were performed at 60°·s-1. Participants wore the bioceramic or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 27 publications
(50 reference statements)
3
23
0
2
Order By: Relevance
“…A total of eleven studies were ultimately identified and included in this review (Table 1). Thereafter, selected studies were classified into two different categories according to their experimental design: six studies investigated the 'effects of FIR-emitting garments worn during exercise' [16,[30][31][32][33][34], and five studies investigated the 'effects of FIR-emitting garments worn post-exercise' [35][36][37][38][39].…”
Section: Plos Onementioning
confidence: 99%
See 4 more Smart Citations
“…A total of eleven studies were ultimately identified and included in this review (Table 1). Thereafter, selected studies were classified into two different categories according to their experimental design: six studies investigated the 'effects of FIR-emitting garments worn during exercise' [16,[30][31][32][33][34], and five studies investigated the 'effects of FIR-emitting garments worn post-exercise' [35][36][37][38][39].…”
Section: Plos Onementioning
confidence: 99%
“…All the studies had samples sizes of five to twenty participants, with only males [30,31,34] or a mixture of female and male participants [16,32,33]. In the studies testing FIR-emitting garments post-exercise, participants were recreationally active [36][37][38] or elite male athletes [35,39], and their age ranged from 19 to 26 years except in one study where the participants were > 60 years old [37]. Sample sizes ranged from 14 to 22 participants.…”
Section: Samplesmentioning
confidence: 99%
See 3 more Smart Citations